Cycle Threshold Values in the Context of Multiple RT-PCR Testing for SARS-CoV-2 - Romero-Alvarez D; Garzon-Chavez D; Espinosa F; Ligña E; Teran E; Mora F; Espin E; Albán C; Galarza JM; Reyes J (Dove Medical Press, 2021)
Daniel Romero-Alvarez,1 Daniel Garzon-Chavez,2 Franklin Espinosa,3 Edison Ligña,3 Enrique Teran,2 Francisco Mora,3 Emilia Espin,4 Cristina Albán,4 Juan Miguel Galarza,4 Jorge Reyes3,5 1Biodiversity Institute and Department of Ecology & Evolutionary Biology, University of Kansas, Lawrence, KS, USA; 2Colegio de Ciencias de la Salud, Universidad San Francisco de Quito, Quito, Ecuador; 3Departamento Microbiología Médica, Hospital IESS Quito Sur, Quito, Ecuador; 4Hospital IESS Carlos Andrade Marin, Quito, Ecuador; 5Universidad Central del Ecuador, Quito, EcuadorCorrespondence: Daniel Garzon-ChavezColegio de Ciencias de la Salud, Universidad San Francisco de Quito, Diego de Robles s/n y Pampite, Cumbaya, Quito, EC170901, EcuadorTel +593 99862409Email dgarzonc@usfq.edu.ecPurpose: Discharge or follow up of confirmed coronavirus disease 2019 (COVID-19) cases depend on accurate interpretation of RT-PCR. Currently, positive/negative interpretations are based on amplification instead of quantification of cycle threshold (Ct) values, which could be used as proxies of patient infectiousness. Here, we measured Ct values in hospitalized confirmed COVID-19 patients at different times and its implications in diagnosis and follow up.Patients and Methods: Observational study between March 17th-May 12th, 2020 using multiple RT-PCR testing. A cohort of 118 Hispanic hospitalized patients with confirmed COVID-19 diagnosis in a reference hospital in Quito, Ecuador. Multiple RT-PCR tests were performed using deep nasal swab samples and the assessment of SARS-CoV-2 genes N, RdRP, and E.Results: Patients’ median age was of 49 years (range: 24– 91) with a male majority (62.7%). We found increasing levels of Ct values in time, with a mean Ct value of 29.13 (n = 61, standard deviation (sd) = 5.55) for the first test and 34.38 (n = 60, sd = 4), 35.52 (n = 20, sd = 2.85), and 36.12 (n = 6, sd = 3.28), for the second, third, and fourth tests, respectively. Time to RT-PCR lack of amplification for all tests was of 34 days while time to RT-PCR Ct values > 33 was of 30 days.Conclusion: Cycle thresholds can potentially be used to improve diagnosis, management and control. We found that turnover time for negativity can be large for hospitalized patients and that 11% cases persisted with infectious Ct values for more time than the current isolation recommendations.Keywords: SARS-CoV-2, coronavirus, pandemic, cycle thresholds, RT-PCR, diagnosis, COVID-19